Elevated air stability in PBDT-DTNT:PCBM solar cells by focusing on roles of fibrillar/patterned nanostructures via graphene/polymer constituents. (1st March 2020) - Liu, Xiaojuan; Ding, Pan; Yuan, Zhihua; Tian, Hui; Jiao, Youzhou; Agbolaghi, Samira
Graphical abstract: Highlights: Morphological, electrochemical, and photovoltaic stabilities of PBDT-DTNT:PC71BM solar cells were promoted. Pre-designed supramolecules were utilized for stability increment. The most stabilized devices were fabricated on the basis of rGO/PBDT-DTNT nanostructures. The PCE decreased from 6.09% for upon-fabricated to 4.87% for 1 month aged systems. Abstract: Morphological, electrochemical, and photovoltaic stabilities of the poly[benzodithiophene-bis(decyltetradecyl-thien) naphthothiadiazole] (PBDT-DTNT):phenyl-C61-butyric acid methyl ester (PC71BM) solar cells were promoted by the pre-designed supramolecules on the basis of reduced graphene oxide (rGO) nanosheets. Nanostructures consisted of the pristine rGO, grafted-rGO/PBDT-DTNT, rGO-polythiophene (GPTh) electrospun nanofiber, grafted-rGO/PBDT-DTNT electrospun nanofiber and rGO/PBDT-DTNT samples. The reduction in photovoltaic characteristics during air aging was the steepest for the unmodified PBDT-DTNT:PC71BM solar cells. From rGO based photovoltaics towards the rGO/PBDT-DTNT modified ones possessing the well-patterned PBDT-DTNT nanofibers, the slopes of graphs decreased. The most stabilized devices were fabricated on the basis of PBDT-DTNT:PC71BM:rGO/PBDT-DTNT active layers (power conversion efficiency (PCE) from 6.09% for upon-fabricated to 4.87% for 1 month aged systems) for having the most red-shifted and intensified absorbance, the largest phase separation, the lowest impedance responses and the highest photovoltaic characteristics during 1 month air aging (short circuit current density (Jsc ) of 12.09 mA/cm 2, fill factor (FF) of 63%, open circuit voltage (Voc ) of 0.64 V, hole mobility (µh ) of 5.3 × 10 –5 cm 2 /V s, electron mobility (µe ) of 7.9 × 10 –4 cm 2 /V s, charge transfer resistance (Rtr ) of 431 Ω cm 2 and PCE of 4.87%). The GPTh/PBDT-DTNT/PC71BM (Jsc = 10.31 mA/cm 2, FF = 49%, Voc = 0.55 V, Rtr = 796 Ω cm 2 and PCE = 2.78%) and grafted-rGO/PBDT-DTNT/PBDT-DTNT (Jsc = 10.98 mA/cm 2, FF = 56%, Voc = 0.60 V, Rtr = 539 Ω cm 2 and PCE = 3.69%) electrospun nanofibers also imparted the stabilization of devices within 1 month.